The Effect of Price and Service Quality on Customer Satisfaction at Cafe Dema Gontor Campus 2 - Noviana Prasanti; Alfin Natiqul Mahmud; Ahmad Suminto; Muhammad Jafar (Universitas Darussalam Gontor, 2024)
Cafe Dema is a significant and influential economic factor. Its role at Pondok Modern Darussalam Gontor Campus 2 is to be a driver, supporter, and driver of economic growth. Cafe Dema also has important duties and responsibilities at Pondok Modern Darussalam Gontor Campus 2 in improving the economy of Gontor Campus 2 students and stabilizing student activities at Gontor Campus 2. As a result, the cottage has a Cafe Dema business to support these activities. Cafe Dema specializes in hearty fare. Many efforts have been made to attract customers, one of which is to improve service quality. As a result, the café dema staff takes special care of the service that customers enjoy. This is done to ensure that customers are happy with the service they received. A descriptive quantitative research model is used in this study. Interviews and questionnaires were used to collect primary data. Random sampling is used in the sampling technique. Multiple linear regression with SPSS statistics 26 is the data analysis technique used. Based on previous research, it is known that the variables of service quality and price affect customer satisfaction at Café Dema. This is shown based on the results of the f test above, it can be seen that the value of Sig. 0.000 < 0.05 besides that there is a calculated f value of 106.965 while f table 2.69 then it can be concluded that there is a simultaneous influence between the free variables on the bound variable, this is because the significance value is smaller and the calculated f is greater than the table f. For subsequent researchers it is advisable to add other independent variables besides the quality of service, to further complement this study since there are still other independent variables outside of this study that can affect consumer satisfaction and loyalty. Keywords: Quality of Service, Price, Customer Satisfaction